Экспериментальное обоснование метода измерения сопротивления заземляющего устройства - Нижевский, Илья Викторович; Нижевский, Виктор Ильич; Бондаренко, Владимир Емельянович (НТУ "ХПИ", 2016)
Рассмотрены экспериментальные исследования трехэлектродной установки для измерения сопротивления заземляющих устройств различного назначения. На основе использования метода физического моделирования представлено экспериментальное обоснование метода измерения сопротивления заземляющего устройства любой конструкции в произвольной структуре грунта. По результатам моделирования решена система уравнений шестого порядка, что позволило определить собственные и взаимные сопротивления в трехэлектродной установке с достаточно высокой точностью и без отыскания точки нулевого потенциала.

Purpose. The paper considers experimental research of threeelectrode units for measuring the resistance of grounding devices for different purposes. Methodology. The experimental study of the method of resistance measurement of grounding devices for any design in any soil structure using the method of physical modeling is presented. Results. By results of model operation the set of equations of the sixth order is solved. It allowed to determine the own and mutual impedance in the three-electrode unit with high accuracy without searching the point of zero potential. Features of measuring and defining the own and relative resistances of various combinations of electrodes for three-electrode measuring unit are considered. Originality. The necessity of finding a zero potential point is excluded. Practical value. The proposed method provides the smallest possible spacing of potential electrodes outside the grounding devices. This reduces the wiring length measurement circuit in several times, increases the ratio "signal – noise", removes the restrictions on building of the territory outside the test grounding device.
The experimental validation of the grounding device resistance measurement method
Keywords: экспериментальные исследования; заземляющее устройство; метод измерения сопротивления; трехэлектродная установка; метод физического моделирования; экспериментальное обоснование; experimental research; grounding device; resistance measurement method; three-electrode unit; method of physical modeling; experimental validation